2020
DOI: 10.1051/bioconf/20201700063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various biological control agents (BCAs) on drought resistance and spring barley productivity

Abstract: The aim of the article is to study the effect of various biological agents of biofungicides on plant resistance to drought and formation of spring barley crops. Endophytic bacteria (Bacillus subtilis), rhizospheric bacteria (Pseudomonas fluorescens), actinomycetes (Streptomyces sp.), and micromycetes (Trichoderma viride) were used as bioagents of biofungicides. Preparations based on biological agents were used to treat spring barley seeds. The studies were carried out in laboratory and field conditions. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Before the experiment, the soil had pHKCl 5.1, humus content was 3.28% (according to Kirsanov). The experiment was conducted by Dospekhov's method [2]: the number of options was 5, different doses of fertilizers were used over 28 years. The repetition of the experiment was 4-fold, the placement of variants was complicated, the size of the plot was 14m x 10m, the area of the plot was 140 m 2 , the accounting area for two-factor studies was 24 m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the experiment, the soil had pHKCl 5.1, humus content was 3.28% (according to Kirsanov). The experiment was conducted by Dospekhov's method [2]: the number of options was 5, different doses of fertilizers were used over 28 years. The repetition of the experiment was 4-fold, the placement of variants was complicated, the size of the plot was 14m x 10m, the area of the plot was 140 m 2 , the accounting area for two-factor studies was 24 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The yield depends on the integrated use of mineral fertilizers, whose consumption is determined by the stage of development and maturation of the crop and the composition of the soil, its fertility, meteorological conditions, and the level of moisture, which affects the efficiency of fertilizing [2,3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Органика в чистом виде экологична и почти безвредна, но не сбалансирована по составу. Кроме того, легко ошибиться с дозировкой, получив нейтральный или отрицательный эффект [3,4]. Минеральные удобрения выпускаются предприятиями с учетом потребностей культур и сезонности внесения и требуют точного соблюдения дозировок.…”
Section: Introductionunclassified
“…induced systemic resistance by stimulating these genes. Induced resistance is persistent and generally nonspecific to biotic and abiotic constraints (Safin et al 2020;. Phoka et al (2020) and Safin et al (2020) revealed that the treatment with Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%
“…Induced resistance is persistent and generally nonspecific to biotic and abiotic constraints (Safin et al 2020;. Phoka et al (2020) and Safin et al (2020) revealed that the treatment with Trichoderma spp. increased catalase and peroxidase activities and that this increase could be related to lignification.…”
Section: Introductionmentioning
confidence: 99%